Influence of arbuscular mycorrhizal fungi and the expression of K+/Cs+ transporters on the accumulation of caesium by plants - Wiesel, Lea (2011)
Radiocaesium (134Cs, 137Cs) is of environmental concern because of its incorporation into the food chain and prolonged emission of harmful radiation. Plants take up caesium via cation transporters which cannot discriminate between radioactive and stable caesium (133Cs). Around 80% of angiosperms live in symbiosis with arbuscular mycorrhizal (AM) fungi that deliver mineral nutrients to their hosts. Contrasting effects of AM fungi on caesium accumulation by plants have been reported. The ultimate aim of this thesis was to determine whether AM fungi reduced caesium accumulation in Medicago truncatula by down regulating the expression of plant genes encoding specific potassium transporters through improving potassium nutrition of their hosts. Accumulation of potassium and stable caesium by non mycorrhizal and mycorrhizal Medicago truncatula was studied, and the effects of caesium and AM fungi on plant gene expression were investigated. In these experiments, shoot potassium concentrations of non mycorrhizal and mycorrhizal plants were identical. However, in some experiments AM associations decreased shoot caesium concentrations. These observations were also true for five other plant species studied. Colonisation of Medicago truncatula with Glomus sp. influenced expression of some genes encoding cation transport proteins, but the expression profile did not suggest improved potassium nutrition. The presence of caesium also affected the expression of several putative cation transporters, but the consequences of these changes are unknown. A reduced colonisation rate of Medicago truncatula by Glomus intraradices was observed at caesium concentrations that exist in the rhizosphere. In conclusion, in these experiments, AM fungi did not improve plant potassium nutrition, and there was no evidence that AM fungi reduced caesium accumulation by down regulating expression of plant genes encoding potassium transporters. Although colonisation by AM fungi can reduce shoot caesium concentrations, this was not always observed. Thus, fungal inoculation cannot be relied upon to deliver crops with reduced radiocaesium concentrations.